LOGO-TEKNIK IKLAN NAN CITRA NEGATIF - Sihabul Millah (Jurnal Sosiologi Reflektif, 2014)
This paper studies various kinds of ads that attract women as target. Using Rollan Bartrès’s model of analysis, the results showed that the logo-techniquesin advertising work well to raise the basic human instincts, such as the instincts of intimacy, sex, fear, and the idols that has strong effect to women.